EX-SITU GROWTH RATE OF MONTIPORA AND ECHINOPORA CORALS IN THE CORAL BREEDING FACILITY OF PT. TIRTA SAMUDRA BALI, DAWAN DISTRICT, KLUNGKUNG REGENCY, BALI - Ishaq, Syafrial Yanuar; Isdianto, Andik; Septiandi, Adrian Rahman (Directorate of Research and Community Service (DRPM), 2023)
The phylum Coelenterata, class Anthozoa, includes a group of marine living things known as corals. Corals feature a variety of incredibly gorgeous colors and patterns. The majority of the world's more than 70,000 coral species may be found in tropical marine environments. Due to its geographic setting, Indonesia has an extremely high level of coral diversity and is the world's largest exporter of ornamental coral. Demand on the market for natural ornamental corals is now rising, along with trends in the rate of industrial development. Allowing this industrial activity to grow will result in huge exploitation and put the coral reef environment at danger. Therefore, to quickly increase the number of corals, this research examined transplantation methods. The montipora and echinopora genera were the focus of this study. The Montipora capricornis coral sample from PT Tirta Samudra Bali had the highest growth rate of the Montipora genus corals there, with an average growth rate of 1,404 cm2/week. The highest growth rate of the Echinopora genus corals had an average growth rate of 0.362 cm2/week. As they have a 100% survival record, cultivation activities using the transplant method performed at PT. Tirta Samudra Bali are regarded as successful